Successful instructional leadership practices in challenging circumstances: a case study of one Qwaqwa township secondary school - Mofokeng, Lehlohonolo Israel (My University, 2017)
This study sought to explore successful instructional leadership practices in challenging circumstances. One township secondary school located in QwaQwa, Free State province, was used as the case study. The purpose of this study was to understand how the school has managed to consistently produce meritorious academic performances over the years despite facing multiple deprivations such as poverty, high crime rates and dilapidated learning infrastructure, among others. To better understand the instructional leadership approach, the study identified three key characteristics of successful instructional leaders and used them to form the basis for understanding whether the identified school principal applied them in responding to their learners‘ socio-economic challenges. This study was located within qualitative methodological approach with interpretivism as the research paradigm. The main data source was the in-depth interviews. The participants included the principal, head of department and two senior teachers. The study found the following to be key to the school‘s consistent plausible academic performance: (a) the main focus of the school was on ensuring the availability and efficient use of the instructional materials (b) the school principal took professional development of his academic staff seriously (c) there was a strong focus on managing teaching and learning (d) goal setting was seen as a driver towards achieving the academic goals of the school and (e) the effective use of the school‘s allocated instructional time was of great importance.
Submitted in accordance with the partial requirements for the degree of Master of Education at the University of the Witwatersrand February 2016
Keywords: Educational leadership--South Africa; Leadership--South Africa; High schools--South Africa--Qwaqwa--Administration; High school principals--South Africa--Qwaqwa; Education--South Africa; School management and organization--South Africa